Multi-objective optimization of structures topology by genetic algorithms - Madeira, JFA (2018)
This work develops a computational model for topology optimization of linear elastic structures for situations where more than one objective function is required, each one of them with a different optimal solution. The method is thus developed for multi-objective optimization problems and is based on Genetic Algorithms. Its purpose is to evolve an evenly distributed group of solutions (population) to obtain the optimum Pareto set for the given problem. To reduce computational effort, optimal solutions of each of the single-objective problems are introduced in the initial population. Two numerical examples are presented and discussed to assess the method.